Creating a R.A.F.T to engage teenage parents back into education: A case study - Subban, Pearl; Round, Penny; Fuqua, Melyssa; Rennie, Jennifer (Frontiers in Education, 2022)
Through the use of a case study, this paper explores the provision of educational and support services to a group of marginalised young parents in Melbourne, Australia. Teenage parents present as a vulnerable population, and are at risk of becoming socially, economically and culturally disadvantaged. However, young parent support programs, such as the program under study in this project, act as rafts, providing a much-needed lifeline to student participants. These programs engage young parents back into education, after withdrawal due to pregnancy, and increase their likelihood of a life without social disadvantage. Utilising one site from the young parents program, this study examined the educational and support provision to young parents, through a strengths-based, social justice lens. The study yielded the RAFT framework, which may be used to better position young parents to tackle the challenges of their dual roles. Targeting educational providers, teachers and community organisations, the projects attempts to reduce social distance and barriers for the participants.